2017
DOI: 10.1038/s41598-017-16152-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Co-expression Analysis of the SnRK2 Gene Family in Sugarcane (Saccharum officinarum L.)

Abstract: In plants, both abscisic acid (ABA) dependent and independent pathways form the basis for the response to environmental stresses. Sucrose non-fermenting 1-related protein kinase 2 (SnRK2) plays a central role in plant stress signal transduction. However, complete annotation and specific expression patterns of SnRK2s in sugarcane remain unclear. For the present study, we performed a full-length cDNA library survey of sugarcane, thus identifying ten SoSnRK2 genes via phylogenetic, local BLAST methods, and variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 57 publications
4
20
0
Order By: Relevance
“…However, in agreement with our analysis in S . viridis , SnRK2 genes from subclasses I and II were upregulated in the phylogenetically related plant sugarcane ( Saccharum officinarum ) submitted to NaCl and PEG treatments 48 . In addition, subclass II SnRK2s 2.7 and 2.8 from Arabidopsis, which have high orthology with SvSnRK2.4, have been demonstrated to participate in the regulation of some drought-responsive genes involving the ABA-responsive element binding factors AREB/ABF 49 .…”
Section: Discussionmentioning
confidence: 99%
“…However, in agreement with our analysis in S . viridis , SnRK2 genes from subclasses I and II were upregulated in the phylogenetically related plant sugarcane ( Saccharum officinarum ) submitted to NaCl and PEG treatments 48 . In addition, subclass II SnRK2s 2.7 and 2.8 from Arabidopsis, which have high orthology with SvSnRK2.4, have been demonstrated to participate in the regulation of some drought-responsive genes involving the ABA-responsive element binding factors AREB/ABF 49 .…”
Section: Discussionmentioning
confidence: 99%
“…It is expected that the signaling pathway relaying ABA stimuli is also conserved in monocot plants. Supporting this hypothesis, recent studies have shown that ABA strongly activates expression of SnRK2 counterparts in sugarcane (Li et al, 2017). Here we confirmed that three functional SnRK2 proteins—ScSAPK8, ScSAPK9, and ScSAPK10—are encoded by the sugarcane genome, further suggesting that the ABA-response pathway is conserved in both mono- and eudicotyledons.…”
Section: Discussionmentioning
confidence: 85%
“…officinarum hybrid cultivar ) using homologous protein sequences from A. thaliana and Sorghum bicolor . Based on previous studies in monocots and eudicots, these were designated ScSAPK8, ScSAPK9, and ScSAPK10 (Boudsocq et al, 2004; Kobayashi et al, 2004; Fujii et al, 2009; Fujita et al, 2009; Li et al, 2010; Cai et al, 2014; Li et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although they obtained substantial results considering the limited resources available at the time, these authors reported a relatively low number of PKs (510) in sugarcane. Other studies have indicated that sugarcane PKs are involved in this plant's development and response to environmental stimuli, such as salt, cold and drought stresses (Carraro et al, 2001;Pagariya et al, 2012;Li et al, 2017). Even more relevant is the compelling evidence that a leucine-rich repeat (LRR) receptor-like kinase is related to sucrose-accumulating sugarcane tissues and genotypes, indicating its involvement in the regulation of sucrose synthesis in mature leaves of this sugar crop (Vicentini et al, 2009).…”
Section: Introductionmentioning
confidence: 99%